2005
DOI: 10.1017/s1464793105006780
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and morphological supertree of stony corals (Anthozoa: Scleractinia) using matrix representation parsimony

Abstract: The supertree algorithm matrix representation with parsimony was used to combine existing hypotheses of coral relationships and provide the most comprehensive species-level estimate of scleractinian phylogeny, comprised of 353 species (27% of extant species), 141 genera (63%) and 23 families (92%) from all seven suborders. The resulting supertree offers a guide for future studies in coral systematics by highlighting regions of concordance and conflict in existing source phylogenies. It should also prove useful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 77 publications
3
72
3
Order By: Relevance
“…Kerr, A. Baird, T. Hughes, submitted) found that transitions between sexuality occur about half as frequently as transitions between reproductive modes. Using a "supertree" phylogeny (Kerr 2005) of 242 species of scleractinian corals for which data on both sexuality and mode of reproduction were available, they also found that transitions from brooding to spawning outnumbered reverse transitions by more than two to one. The analysis overwhelmingly supported gonochorism as the ancestral sexual state, but was ambiguous as to reproductive mode (Figure 2).…”
Section: Systematic Patterns In Scleractinian Reproductive Traits In mentioning
confidence: 99%
See 2 more Smart Citations
“…Kerr, A. Baird, T. Hughes, submitted) found that transitions between sexuality occur about half as frequently as transitions between reproductive modes. Using a "supertree" phylogeny (Kerr 2005) of 242 species of scleractinian corals for which data on both sexuality and mode of reproduction were available, they also found that transitions from brooding to spawning outnumbered reverse transitions by more than two to one. The analysis overwhelmingly supported gonochorism as the ancestral sexual state, but was ambiguous as to reproductive mode (Figure 2).…”
Section: Systematic Patterns In Scleractinian Reproductive Traits In mentioning
confidence: 99%
“…Using more recently compiled generic records of fossil occurrence and a more complete data set of coral reproductive traits, Baird and colleagues (A. Baird, A. Kerr, M. Kosnik, submitted) demonstrated that there was, in fact, no association between either sexuality or mode of reproduction and extinction in the Oligocene. They concluded, Figure 2 (a,b) Sexual system (light blue, hermaphroditic; orange, gonochoric) and reproductive mode (red, brood planulae; green, spawn gametes) in 289 species of scleractinian corals mapped onto the supertree phylogeny of Kerr (2005). …”
Section: Biogeographical and Evolutionary Patterns In The Relative Abmentioning
confidence: 99%
See 1 more Smart Citation
“…(b) Phylogeny and taxonomy We used the largest available phylogeny of Scleractinia [18]. Large phylogenies possess more detailed character information and the statistical power to consider more complex patterns of character evolution [19].…”
Section: (A) Reproductive Datamentioning
confidence: 99%
“…11 Subclade C1 contains representatives from several coral families and may correspond to a grouping of these families into one of the Robusta subclades in accordance to the novel coral phylogeny. 11,28 Subclade C2 contains green and cyan proteins from Archaeocoeniina suborder (families Acroporidae and Pocilloporidae) and a cyan protein from the sea anemone A. majano (amajCFP, original name amFP486). 11 The C3 subclade is again a mixture of coral suborders.…”
Section: Phylogenetical Analysismentioning
confidence: 99%